TEACHING MACROECONOMICS IN UNDERGRADUATE ADMINISTRATION COURSES - Behrens, Alfredo (2013)
The relative unimportance enade (the National Student Performance Exam) places on macroeconomics coupled with the long time that elapses between graduation and the professional demands for its understanding combine to act against the interests of the discipline undergraduate administration courses. However, an understanding of macroeconomics develops students’ aptitude for strategic and tactical thinking and shapes better citizens. This paper demonstrates how providing opportunities for students to participate more actively in learning can neutralize their resistance. This began through analyzing homework tasks in class, with the aim of better understanding the factual and emotional meanings of unemployment to families and society. Videos and photographs of the Great Depression and the contemporary ones in Europe, including the Indignados and Geração à Rasca movements, in Spain and Portugal, respectively, also served the purpose. This was followed by Aggregate Demand and Supply, presented before the national accounts, which in turn came soon after the macroeconomic model for closed economies, followed by the model for open economies, business cycles, inflation and an analysis of the Real Plan; including videos on the period of hyperinflation. The course closed with a role-playing game in which students called a press conference to express their views on the expansionist policies of the Brazilian government during the first half of 2012, from the position of the interest group of their choice.